Activation of a hybrid twinning mechanism in a Cr-Ni-Si-V-N medium manganese austenitic steel containing precipitates. (February 2021) - Shyamal, S.; Farahani, M. Ghiasabadi; Allam, T.; Hamada, A.S.; Haase, C.; Kömi, J.I.; Chakraborti, P.C.; Sahu, P.
Abstract: Twinning nucleation in a medium Mn austenitic steel containing precipitates is studied at low strain 0.02, using transmission electron microscopy. In the near vicinity of the precipitates, unfaulting dislocation reaction is favored, while twinning is activated farther from the precipitates. Twin nucleation follows a hybrid mechanism, involving creation of stacking faults through classical dislocation dissociation, while those stacking faults subsequently overlapped following a non-classical alternated stacking fault pair mechanism to create a three-layer twin nucleus. The observed twinning behavior is interpreted from an energy barrier variation viewpoint within the matrix. Graphical abstract: Image, graphical abstract